Advantages and Disadvantages of Neoadjuvant Chemotherapy in Muscle-Invasive Bladder Cancer - Farzad Allameh; Hojjati, Seyyed Ali (Archives of Men's Health, 2025)
Neoadjuvant chemotherapy (NAC) has been a standard treatment in the management of muscle-invasive bladder cancer (MIBC), especially for cisplatin-eligible patients. However, its widespread adoption is hampered by unresolved controversies. Various systematic reviews and meta-analyses support the role of NAC in improving survival. While in a meta-analysis published by Li G and colleagues in 2017, no difference in Overall Survival (OS) was observed between the group receiving NAC and the group that did not receive NAC (1). In addition to its advantages, it is necessary to examine its possible disadvantages and challenges.